2021
DOI: 10.1002/ptr.7254
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and antihyperlipemic of spirulina (Arthrospira platensis) sauce on patients with hypertension: A randomized triple‐blind placebo‐controlled clinical trial

Abstract: Systemic arterial hypertension is an independent risk factor for coronary heart disease, stroke, heart failure, and chronic kidney diseases. Spirulina is microalgae with nutritious ingredients and has potential attenuating effects on chronic diseases including hypertension. Spirulina can be added to food products in order to develop functional foods. The aim of this study was to assess the effects of 8-week consumption of a salad dressing containing 2 g of spirulina platensis powder versus a placebo dressing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Systolic blood pressure decreased significantly compared with placebo, with a higher reduction in the subjects with borderline hypertension than in the subjects with high-normal blood pressure [64]. A randomized triple-blind placebo-controlled clinical trial study conducted by Ghaem et al [65] in 2021 involved 41 patients with hypertension consuming a salad dressing containing 2 g of Spirulina platensis powder for two months. The results showed that the Spirulina dressing significantly decreased systolic blood pressure, diastolic blood pressure, serum triglyceride, total cholesterol, and low-density lipoprotein (LDL) levels in comparison to placebo controls [65].…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Systolic blood pressure decreased significantly compared with placebo, with a higher reduction in the subjects with borderline hypertension than in the subjects with high-normal blood pressure [64]. A randomized triple-blind placebo-controlled clinical trial study conducted by Ghaem et al [65] in 2021 involved 41 patients with hypertension consuming a salad dressing containing 2 g of Spirulina platensis powder for two months. The results showed that the Spirulina dressing significantly decreased systolic blood pressure, diastolic blood pressure, serum triglyceride, total cholesterol, and low-density lipoprotein (LDL) levels in comparison to placebo controls [65].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…A randomized triple-blind placebo-controlled clinical trial study conducted by Ghaem et al [65] in 2021 involved 41 patients with hypertension consuming a salad dressing containing 2 g of Spirulina platensis powder for two months. The results showed that the Spirulina dressing significantly decreased systolic blood pressure, diastolic blood pressure, serum triglyceride, total cholesterol, and low-density lipoprotein (LDL) levels in comparison to placebo controls [65]. Bioactive compounds and extracts from microalgae for CVDs are summarized in Table 1.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Recently, a randomized, triple-blind, placebo-controlled trial was conducted on 48 hypertensive patients to assess the effects of consuming a salad dressing enriched with 2 g/day of Spirulina powder over 8 weeks in patients with hypertension compared to the placebo group. The results showed that the oral consumption of Spirulina dressing had a significant impact on the reduction in systolic ( p = 0.02) and diastolic ( p = 0.01) blood pressure [ 39 ]. In a similar study conducted by Mickze et al [ 40 ], the authors confirmed the hypotensive effect of Spirulina further.…”
Section: Hypertension and Strokementioning
confidence: 99%
“…Other studies have examined the potential role of Spirulina -fortified dressing or sauce as a functional food. Far and colleagues [ 39 ] emphasized a significant reduction in triglycerides ( p < 0.01) in hypertensive patients when given salad dressing that contained 2 g of Spirulina powder [ 39 ], while the results from the study by Mazloomi et al [ 89 ] confirmed the potential benefits in NAFLD patients. The investigation suggests that sauce prepared with 2 g of Spirulina may improve NAFLD by reducing the grade of fatty liver and liver enzymes (ALT and AST) as well as TG reduction ( p = 0.03) and HDL-C ( p = 0.02) levels increase between baseline and the end of the treatment.…”
Section: Hyperlipidemiamentioning
confidence: 99%